2019
DOI: 10.32098/mltj.04.2019.01
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Suture Materials on Achilles Tendon Metabolism: A Preliminary in vivo Study of mRNA levels in Rabbits

Abstract: Backround. Different suture materials are preferable for the repair of Achilles tendon ruptures. The effect of the sutures on the biological level on a repair scenario is still tentative. The purpose of this study is to show the effects of Vicryl ® , Ethibond ® and PDS ® II on Achilles tendons at mRNA levels. Methods. 36 Achilles tendons of 18 White New Zealand Rabbit were divided into four groups (n:9). Acute tendon rupture model was created and three groups were repaired with each of the aforementioned sutur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In another recently published study on acute Achilles rupture repair by Saxena et al evaluated 188 cases, braided non-absorbable suture was associated with more wound complications (14). Other authors have described effects of different suture in the animal model with Achilles (15). Because of this, authors recommend avoidance of braided non-absorbable suture when possible for Achilles tendon surgery (2,8,14).…”
Section: Discussionmentioning
confidence: 99%
“…In another recently published study on acute Achilles rupture repair by Saxena et al evaluated 188 cases, braided non-absorbable suture was associated with more wound complications (14). Other authors have described effects of different suture in the animal model with Achilles (15). Because of this, authors recommend avoidance of braided non-absorbable suture when possible for Achilles tendon surgery (2,8,14).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory reaction to a bsorbable sutures in tendons may be a matter of concern (14,18,20,74). However, because of relatively quick degradation, inflammatory response to absorbable sutures is shorter than that to non-absorbable ones.…”
Section: Outcomementioning
confidence: 99%
“…In an acute tendon rupture model, Ergun et al performed Achilles tendon repair with different suture materials. It was found that the biological properties of absorbable PDS sutures were superior compared to Vicrl and Ethibond sutures, and the study suggests using absorbable PDS sutures in Achilles tendon repairs (12). Su et al investigated the effect of suture absorbability on enthesis regeneration and biomechanical properties in an acute rotator cuff healing model in rabbits (7).…”
Section: Introductionmentioning
confidence: 99%